Inflammasome-mediated cell death in response to bacterial pathogens that access the host cell cytosol: lessons from legionella pneumophila - Casson, Cierra N.; Shin, Sunny (Frontiers in Cellular and Infection Microbiology, 2013)
Cell death can be critical for host defense against intracellular pathogens because it eliminates a crucial replicative niche, and pro-inflammatory cell death can alert neighboring cells to the presence of pathogenic organisms and enhance downstream immune responses. Pyroptosis is a pro-inflammatory form of cell death triggered by the inflammasome, a multi-protein complex that assembles in the cytosol to activate caspase-1. Inflammasome activation by pathogens hinges upon violation of the host cell cytosol by activities such as the use of pore-forming toxins, the use of specialized secretion systems, or the cytosolic presence of the pathogen itself. Recently, a non-canonical inflammasome has been described that activates caspase-11 and also leads to pro-inflammatory cell death. Caspase-11 is activated rapidly and robustly in response to violation of the cytosol by bacterial pathogens as well. In this mini-review, we describe the canonical and non-canonical inflammasome pathways that are critical for host defense against a model intracellular bacterial pathogen that accesses the host cytosol—Legionella pneumophila.